The Complexity of High School Students' Semiotic Graphics in Solving Statistical Problems - Ahmad Choirul Anam (LP2M Universitas Ibrahimy, 2025)
The ability to represent data graphically is a crucial skill in learning statistics, yet it involves complex semiotic processes that are often influenced by students’ cognitive styles. This study was conducted to explore the semiotic complexity of high school students’ statistical graphs about their cognitive styles: field dependent (FD) and field independent (FI). Using a descriptive qualitative approach, four 12th-grade students were selected based on the Group Embedded Figures Test (GEFT) and a standardized mathematics ability test to ensure cognitive style categorization and equal academic level. Data were collected through a Semiotic Graph Complexity Test (TKSG) and semi-structured interviews focusing on four semiotic components: problems, actions, concepts, and properties.The findings show that students with FI cognitive styles demonstrated a higher level of semiotic complexity, reaching the